Implementation the Indonesian Ulema Council Fatwa regarding the Sale and Purchase of Gold in Installments at Sharia Bank of Indonesia - Cora Elly Noviati; Ana Laela Fatikhatul Choiriyah; Encik Lukmanul Hakim; Gatot Iriyanto; Frandy Risona Tarigan (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
Purchasing gold using an installment payment model or in the form of savings has been applied to Sharia Bank of Indonesia (BSI) (BSI) and Pegadaian products. This started with the issuance of MUI Fatwa Number 77/DSN-MUI/V/2010 concerning the Implementation of Gold Installments, even though there were several ulama' who prohibited the practice of buying and selling gold in installments. Based on this, the author is interested in studying the application of gold installments at Sharia Bank of Indonesia (BSI) and its differences with gold savings transactions implemented by pawnshops, both in terms of contracts, payments and comparison of the installments of the two gold installments. The research method used is normative juridical using a statutory approach and a comparative approach. The theory used is the theory of legal benefit. The results of this research show that the transaction model applied by BSI is in the form of gold installments using a murabahah contract and a rahn contract, while Pegadaian is a gold savings account. These two gold installment models can provide benefits for people who want to invest in gold.